Transcriptomic analysis of the adaptation to prolonged starvation of the insect-dwelling Trypanosoma cruzi epimastigotes - Smircich, Pablo; Pérez-Díaz, Leticia; Hernández, Fabricio; Duhagon, María Ana; Garat, Beatriz (Frontiers in Cellular and Infection Microbiology, 2023)
Trypanosoma cruzi is a digenetic unicellular parasite that alternates between a blood-sucking insect and a mammalian, host causing Chagas disease or American trypanosomiasis. In the insect gut, the parasite differentiates from the non-replicative trypomastigote forms that arrive upon blood ingestion to the non-infective replicative epimastigote forms. Epimastigotes develop into infective non-replicative metacyclic trypomastigotes in the rectum and are delivered via the feces. In addition to these parasite stages, transitional forms have been reported. The insect-feeding behavior, characterized by few meals of large blood amounts followed by long periods of starvation, impacts the parasite population density and differentiation, increasing the transitional forms while diminishing both epimastigotes and metacyclic trypomastigotes. To understand the molecular changes caused by nutritional restrictions in the insect host, mid-exponentially growing axenic epimastigotes were cultured for more than 30 days without nutrient supplementation (prolonged starvation). We found that the parasite population in the stationary phase maintains a long period characterized by a total RNA content three times smaller than that of exponentially growing epimastigotes and a distinctive transcriptomic profile. Among the transcriptomic changes induced by nutrient restriction, we found differentially expressed genes related to managing protein quality or content, the reported switch from glucose to amino acid consumption, redox challenge, and surface proteins. The contractile vacuole and reservosomes appeared as cellular components enriched when ontology term overrepresentation analysis was carried out, highlighting the roles of these organelles in starving conditions possibly related to their functions in regulating cell volume and osmoregulation as well as metabolic homeostasis. Consistent with the quiescent status derived from nutrient restriction, genes related to DNA metabolism are regulated during the stationary phase. In addition, we observed differentially expressed genes related to the unique parasite mitochondria. Finally, our study identifies gene expression changes that characterize transitional parasite forms enriched by nutrient restriction. The analysis of the here-disclosed regulated genes and metabolic pathways aims to contribute to the understanding of the molecular changes that this unicellular parasite undergoes in the insect vector.